PEMBERIAN THERAPY PEMBERIAN MADU UNTUK MENGATASI DIARE DI WILAYAH KERJA PUSKESMAS TANJUNG UNCANG KOTA BATAM - Ditte Ayu Suntara (CV. ADIBA AISHA AMIRA, 2021)
Diarrhea is a serious health problem in developing countries. Diarrhea is the main cause of morbidity and mortality in children under 5 years old. The incidence of diarrhea in Batam City fluctuates and tends to increase in the last 3 years. The incidence of diarrhea in the city of Batam in 2020 from 20 health centers found the highest diarrhea sufferer in toddlers at the Tanjung Uncang Health Center UPT (41.53%) cases. This professional scientific paper aims to see the effect of giving honey to treat diarrhea in toddlers in the Tanjung Uncang Public Health Center, Batam City in 2021. This report uses a case study, while the nursing care provided uses complementary therapy, namely giving honey to treat diarrhea. From the results of the study, it was found that the problem of diarrhea was related to the process of infection, inflammation in the intestines. Nutritional Deficit is associated with Decreased Food Intake, and Knowledge Deficit is related to Lack of Information. The final results showed that there was a decrease in the frequency of bowel movements in An.S, increased appetite, no nausea and vomiting, and the family understood that when given health education about diarrhea, the family was able to change a healthy lifestyle and give honey therapy to children to treat diarrhea 3 times. Administration in one day for 5 days with a dose of 5 ml. Conclusion Therapy Honey can treat diarrhea because honey has flavonoid and polyphenolic molecules that can minimize the frequency of diarrhea and increase body weight. It is recommended for families to make this Honey Giving Therapy as one of the complementary therapies in dealing with diarrhea.